PEMAHAMAN TENTANG BAHAYA NARKOBA DAN ROKOK PADA REMAJA - Marni; Astuti, Endang Puji; Nurrakhmad, Bagus (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: Adolescents have an unstable nature, want to try new things, if family conditions are not harmonious it is feared that these young people try new things dangerous ones, such as smoking, using drugs, and more worrying, becoming drug dealers. Objective: to determine the level of understanding of the dangers of drugs and cigarettes in juveniles in the Wonogiri II Health Center area in March 2019. Methods: The population was class VII and VIII male students in the three schools totaling 586, this study was a random sampling technique, a Cross-Sectional study through questionnaires. Validity test uses the product moment correlation formula. Reliability test using Alpa Cronbach formula. Results: Research Results respondents who had tried smoking 184 people (66.7%), 97 respondents had a very low understanding of smoking (35.1%), understanding of drugs was very low 119 people (43.1%), while high understanding was only 3 respondent (1.1%). Conclusion: Most students in the Wonogiri II Community Health Center work area smoke a lot and have a low level of understanding of the dangers of smoking and drugs, so counseling is needed regarding the dangers of smoking and drugs so that students' behavior away from cigarettes and drugs.